Beyond Convenience: Determinants of E-Wallet Adoption among Generation Z in Lubuk Linggau - Herman Paleni; Arisky Adrinaldo; Ina Gayatri (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study examines the influence of perceived ease of use and risk perception on Generation Z’s behavioral intention to adopt e-wallet services by integrating the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB). Methodology: A quantitative approach was employed using survey data collected from 398 Generation Z respondents in Lubuk Linggau, Indonesia. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM), including the evaluation of measurement model reliability and validity, followed by structural model testing. Results: Perceived Ease of Use has a positive and significant effect on Generation Z's intention to adopt e-wallets, suggesting that simple, user-friendly systems encourage greater adoption. In contrast, risk perception had a significant negative effect, suggesting that concerns about security, privacy, and potential financial loss may reduce users' willingness to adopt e-wallets. Conclusions: Usability and perceived risk jointly influence Generation Z’s decisions to adopt digital payment technology. Limitations: This study was limited to Generation Z in Lubuk Linggau. Future research should include additional variables and broader samples to provide more comprehensive insights into digital payment adoption. Contributions: This study enriches the fintech adoption literature by highlighting the combined roles of usability and risk perception and offers practical insights for improving security, usability, and trust in digital payment systems.